Estructura genética en cinco especies de flebótomos (Lutzomyiaspp.) de la serie townsendi, grupo verrucarum, en Colombia (Diptera: Prychodidae) - Hernández, Claribel; Ruiz García, Manuel; Munstermann, Leonard; Ferro, Cristina (Revista de Biología Tropical, 2008)
Sixteen isoenzyme patterns were analyzed for five Colombian Lutzomyiaspecies. The average unbiased expected heterozygosity levels ranged from 0.098 (Lu. youngi) to 0.215 (Lu. torvida). The five species samples, taken all the isoenzymes employed, were significantly deviated from the Hardy-Weinberg equilibrium by homozygous excess with classical as well as Markov chain exact tests. Possible causes: (1) Wahlund effect within populations due to subdivision and/or sampling. Endogamy could be dis-carded because these loci were affected by highly different levels of homozygous excess. (2) Null alleles could be not discarded, at least for some isoenzymes. The hierarchical Wright ́s F analysis showed high and significant values for each parameter. The average FIT value was 0.655 with a conspicous homozygous excess at a global level (all species taken together); the average FIS value was significantly positive (0.515) as well, with homozy-gous excess within each species. The genetic heterogeneity between the fives species was noteworthy (FST = 0.288), indicating clear genetic differentiation. The more related species pairs were Lu. longiflocosa-Lu. torvida (0.959) and Lu torvida-Lu. spinicrassa (0.960); while Lu. torvida-Lu. youngi (0.805) and Lu. quasitownsendi-Lu. youngi (0.796) were the most divergent (Nei ́s genetic identity matrix). UPGMA and Wagner algorithms showed that the most divergent species was Lu. youngi, whereas the most related were Lu. longiflocosa-Lu. tor-vida and Lu torvida-Lu. spinicrassa. A spatial autocorrelation analysis (Moran ́s I index) revealed a very weak, or inexistent spatial structure, which means that the speciation events between these species were independent from the geographic distances from where they currently live.